2018
DOI: 10.1186/s12939-017-0713-9
|View full text |Cite
|
Sign up to set email alerts
|

Addressing female genital mutilation in Europe: a scoping review of approaches to participation, prevention, protection, and provision of services

Abstract: BackgroundPublic and policy attention to female genital mutilation (FGM) in diaspora communities has increased in Europe, but research remains limited and misinformation abounds. As a first step to addressing these issues, this study explored FGM prevention and response interventions in Europe, using a scoping literature review and key informant interviews.MethodsA scoping study design was selected, using Arksey and O’Malley’s six-stage scoping framework to review identified sources. Key informant interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…People arriving by sea are particularly susceptible to injury and illness; a recent survey of rescue ships found that dehydration and dermatological conditions associated with poor hygiene and crowded conditions were common, as well as new and old traumatic injuries from both violence and accidents 31. The risk of female genital mutilation is high in girls from certain regions and is a recognised reason for seeking asylum 32…”
Section: Resultsmentioning
confidence: 99%
“…People arriving by sea are particularly susceptible to injury and illness; a recent survey of rescue ships found that dehydration and dermatological conditions associated with poor hygiene and crowded conditions were common, as well as new and old traumatic injuries from both violence and accidents 31. The risk of female genital mutilation is high in girls from certain regions and is a recognised reason for seeking asylum 32…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study design was selected, drawing on data from a scoping literature review 21 and interviews (ie, individual and group) with Europe-based academics, legal professionals, statutory and voluntary service providers, community activists and representatives from potentially affected communities. The research question was ‘ What is the role of potentially affected diaspora communities in interventions that respond to and challenge FGM in Europe?…”
Section: Methodsmentioning
confidence: 99%
“…Individual interview participants were recruited purposively to include academics, policy-makers, police officers, NGO staff and community activists in EEA member countries with recognised FGM responses. Initially, interview participants were identified through the literature review 21 (ie, conference presenters and lead authors and other authors appearing in more than one article were invited by email). Additionally, heads of relevant government departments, NGO programme staff and community activists known for their FGM expertise related to one or more of the ‘4P’ focus areas were contacted by phone or email.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is also critically important to distinguish the ethical debate surrounding genital alterations performed on minors, and consider the human right to bodily integrity and genital autonomy of all minors regardless of gender (Brussels Collaboration on Bodily Integrity, 2019; Earp, 2016bEarp, , 2020. This must be further contextualized by the sociopolitical discourse around gender and race which are pivotal to the development of truly unbiased policy (Atallah et al, 2016), failing to do so further "others" non-White migrant women's bodies (Baillot, Murray, Connelly, & Howard, 2018;Johansen, 2017).…”
Section: Attitudes Norms and Control In Fluxmentioning
confidence: 99%
“…Discomfort with genital appearance post-defibulation is further complicated by the fact that re-infibulation is criminalized throughout much of the west. In those nations where legislation does not explicitly outlaw re-infibulation, it is strongly denounced by professional organizations who admonish providers to refuse such patient requests, considering it a form of "medicalized female genital mutilation"; while concomitantly oblivious to the moral double-standard that condones female genital cosmetic surgery (FGCS) among consenting, wealthy women (Ahmadu, 2017;Baillot et al, 2018;Earp, 2016a;Johansen, Ziyada, Shell-Duncan, Kaplan, & Leyed, 2018;Perron, Senikas, Burnett, & Davis, 2020), despite the lack of long-term safety and efficacy data (Barbara et al, 2017;Magon & Alinsod, 2017;Perron et al, 2020;Serati, Salvatore, & Rizk, 2018). Since both reinfibulation and FGCS are primarily performed on consenting adults, we argue that "partial" re-infibulation/"partial" defibulation 5 should be reconsidered as FGCS rather than FGC among women with otherwise healthy sexual function and autonomy in requesting vulvar reconstructive procedures (Shahvisi & Earp, 2019).…”
Section: Attitudes Norms and Control In Fluxmentioning
confidence: 99%